Principles of tourism 1 - Santos, Buen; Manzano, Ronald G. (Quezon City, 2009)
The book contains several chapter. The early chapters discuss the basic concepts and terminologies essential in understanding the tourism industry. There is also an overview of the different components of the tourism industry and a substantial explanation of the tourism system. The book concludes with a coverage of international and local tourism organizations, as well as travel trends and prospects in the 21st century.
Keywords: Tourism; Tourism- Philippines